(3QSGdI aj JMbjb GdGSJYGQI GdJeKdjdI hfbd eG LQi ajgG ef GdHMK Hjf GdJaJGRGfi hGdSjO GdLQLGfis - (3GHf UOQ GdOjfs
(3ChdgG (B:s
(3ef GdahGFO GdNGbGfjI dGHf UOQ GdOjf eSCdI ai JMbjb GdGSJYGQI s
(3BNQgG (B:s
(3Cf dGjLhR chf hLg GdTHg Je s
(3Vef eLehY , JQJjHgG (B: (3ef U (B26 - (3U(B29s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B128(3e(B) s
Keywords: (3GdHdGZIs